2010
DOI: 10.1007/s00330-010-1940-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced magnetic resonance angiography (MRA): evaluation of three different contrast agents at two different doses (0.05 and 0.1 mmol/kg) in pigs at 1.5 Tesla

Abstract: Full-dose gadolinium MRA results in higher image quality and significantly higher SNR compared with the half dose. Gadobutrol and Gd-BOPTA have similar enhancement properties at full dose but at half dose, gadobutrol appears superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…32 Thus, our study shows that the mean SNR was higher for TR-MRA with 3 mL of GBCA compared with CE-MRA (194.4 Ϯ 77.3 for CE-MRA, 199.7 Ϯ 82.9 for TR-MRA, P ϭ .004) and an increased SNR of TR-MRA with a dose of 3 mL led to a similar score of image quality of arterial visualization compared with CE-MRA. Voth et al 33 demonstrated that full-dose gadolinium MRA results in higher SNR compared with a half dose. With regard to TR-MRA, the SNR increased as the dose increased (199.7 Ϯ 82.9 for a dose of 3 mL, 170.8 Ϯ 71.0 for a dose of 2 mL, and 107.7 Ϯ 43.7 for a dose of 1 mL).…”
Section: Discussionmentioning
confidence: 99%
“…32 Thus, our study shows that the mean SNR was higher for TR-MRA with 3 mL of GBCA compared with CE-MRA (194.4 Ϯ 77.3 for CE-MRA, 199.7 Ϯ 82.9 for TR-MRA, P ϭ .004) and an increased SNR of TR-MRA with a dose of 3 mL led to a similar score of image quality of arterial visualization compared with CE-MRA. Voth et al 33 demonstrated that full-dose gadolinium MRA results in higher SNR compared with a half dose. With regard to TR-MRA, the SNR increased as the dose increased (199.7 Ϯ 82.9 for a dose of 3 mL, 170.8 Ϯ 71.0 for a dose of 2 mL, and 107.7 Ϯ 43.7 for a dose of 1 mL).…”
Section: Discussionmentioning
confidence: 99%
“…Gadobutrol is an extracellular macrocyclic gadolinium chelate [17]. Its main feature is its high concentration, which is double the concentration of other contrast agents (1.0 mol/L vs 0.5 mol/L); this allows improved image quality, as shown in both human and animal MR angiography studies [18][19][20][21][22]. Other favorable features are its high T1 relaxivity (5.6), which improves enhancement and image quality and its low osmolality (1.6), which improves tolerability [17].…”
Section: Intraindividual Comparison Of Gadobutrol and Gadopentetate Dimeglumine For Detection Of Myocardial Late Enhancement In Cardiac Mmentioning
confidence: 99%
“…This low of a dose seems likely to be feasible for renal artery MRA as well. When utilizing sub-single doses, the enhancement properties of the contrast agents becomes more important as shown in an animal study where half dose gadobutrol was found superior to Gd-DTPA and Gd-BOPTA [ 32 ].…”
Section: Contrast Agentsmentioning
confidence: 99%